A cluster approach to the formation of tourism destinations in Western Ukrainian cross-border regions - Kyfyak, Vasyl; Kyfyak, Olexander (Turyzm/Tourism, 2021)
The research aims at exploring western Ukrainian cross-border regions where many natural recreational resources, historical, cultural and architectural monuments, a developed transport infrastructure, strong ethnic ties and wide opportunities for tourism flows from the cross-border regions of neighboring countries are found. To achieve this goal, the authors studied foreign experience, in particular the processes of the creation and operation of clusters in Romania and Poland which helped to identify certain stages of development of tourism destinations based on a cluster approach. Comparison of the activities of already established tourism clusters in Ukraine and abroad has helped to establish a list of major business structures that might become a part of a cluster and be involved in the formation of a tourism destination. Based on an analysis of natural and recreational potential, and cultural and historical heritage in western Ukrainian cross-border regions, possible profiles of tourism destinations, and the interest of tourist and other enterprises to be brought together into tourism clusters, are determined, and this has been confirmed by a survey